How are public spaces sustaining cultural identities in the context of China’s increasingly globally focused urban developments: using a case study of Putuo in Shanghai - Choi, Hee Sun (Sunny) (Journal of Architecture and Urbanism, 2016)
This paper explores what it means for a public space to embody the city within rapid urban change in contemporary urban development and how a space can accomplish this by embracing the culture of the city, its people and its places, using the particular case of Putuo, Shanghai in China. The paper employs mapping and empirical surveys to learn how the local community use the act of communal dance in everyday public spaces of this neighborhood, and seeks not to ﬁnd generalizable rules for how humans comprehend a city, but instead to better understand how local inhabitants and their chosen activities can influence their built environment. The findings from this emphasize the importance to identify how public spaces can help to define cities with China’s emerging global presence, whilst addressing the ways in which local needs and perspectives can be preserved.